Meningkatkan Kinerja Guru: Peran Penting Lingkungan Kerja, Manajemen Pembelajaran, dan Aktivitas Mengajar sebagai Penggerak Utama Keunggulan Pendidikan - Agoes Windarto; Muhammad Yanuar Hariyawan (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2025)
Teacher performance is a decisive factor in achieving educational excellence, yet it is strongly influenced by contextual elements such as the work environment, learning management, and the effectiveness of teaching activities. This study investigates the direct and indirect effects of these factors, focusing on the mediating role of teaching activity. Using a quantitative descriptive–correlational design with Structural Equation Modeling (PLS), data were collected from 75 teachers through a structured questionnaire. The results show that the work environment significantly affects teaching activity (β = 0.608, p < 0.05) and teacher performance (β = 0.111, p = 0.027), while learning management strongly influences both teaching activity (β = 0.261, p < 0.05) and teacher performance (β = 0.561, p < 0.05). Teaching activity itself positively impacts teacher performance (β = 0.323, p = 0.015) and mediates the relationship between work environment and teacher performance (β = 0.196, p = 0.033) as well as between learning management and teacher performance (β = 0.084, p = 0.005). The conclusion of this study show that optimizing both the work environment and learning management, alongside promoting active teaching practices, can substantially improve teacher performance.